Performance Analysis For Wireless G (IEEE 802.11 G) And Wireless N (IEEE 802.11 N) In Outdoor Environment - Fadilah, Suzi Iryanti; Shibghatullah, Abdul Samad; Abal Abas, Zuraida; Abd Wahab, Mohd Helmy; Hashim, Wan Nur Wahidah (Asian Research Publishing Network (ARPN), 2014)
-